HEALTH CARE SATISFACTION OF PATIENTS COVERED BY NATIONAL HEALTH INSURANCE IN WAINGAPU, SUMBA TIMUR, INDONESIA - Windi, Yohanes Kambaru; Asnani; Harnani, Baiq Dewi (Universitas Airlangga, 2025)
Introduction: Membership in Indonesia's National Health Insurance (NHI) has dramatically increased, especially among the subsidized poor group, reaching 83.9% of the 229.9 million people enrolled in the scheme. However, patients’ satisfaction with care provided under this coverage remains uncertain. Aims: To measure the health care satisfaction of patients covered by the NHI in Waingapu, Sumba Timur District, East Nusa Tenggara Province, Indonesia. Method: An explanatory cross-sectional study was conducted with 500 patients recruited from three hospitals and 10 community health centers. The Patient-Perceived Indicators of Satisfaction (PPIS) tool was developed for data collection. Descriptive statistical analysis was used to evaluate satisfaction level, while confirmatory factor analysis (CFA) tested the strength of association between indicators and patient satisfaction. Results: Most patients were very satisfied with the health care received; reliability (62%), assurance (52.2%), empathy (56.4%), tangible (49.6%), and responsiveness (45.4%). The CFA confirmed key indicators, including the availability of medicines as central to reliability (0.771), effective medicine (0.788), availability of parking area (0.814) for tangibles, motivation provided by health staff (0.804) for empathy, and responsiveness of pharmaceutical services (0.782). Among all dimensions, patients reported the highest satisfaction in assurance of health care (0.950), while satisfaction on tangible aspects (0.874) received the lowest rating. Conclusion: The study concludes that patients covered by the NHI are satisfied with the expected quality of health care services. However, satisfaction levels vary across individual indicators and dimensions.